Evaluation of salt-tolerance in finger millet (Eleusine coracana) genotypes at seedling stage* - SHAILAJA, H B; THIRUMENI, S (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2005 to evaluate 19 finger millet (Eleusine cracana L. Gaertn.) genotypes for their response to salinity at seedling stage under laboratory conditions. Significant difference was observed anlong the genotypes at different stress levels. All the 5 traits, viz germination, root length, shoot length, seedling length and vigour index declined with increasing salt stress in all the genotypes. However, ’CO 12’, ’GPU 48’, ’Indaf 5’ were highly tolerant, while ’CO 11 ’ was highly susceptible.